The peculiarities of medical care organizing forpatients with viral hepatitis in Ukraine - Vasyl Mykolayovych Mykhalchuk; Valeriy Anatoliyovych Pishchikov (Kazimierz Wielki University, 2020)
The problem of chronic viral hepatitis is gaining relevance. Many authors consider the issues of epidemiology as well as medical and diagnostic problems. Revising the structure of health care facilities (HCFs), a lack of specialized medical care units was defined. The purpose of the Program is to ensure access of the general population to the prevention, diagnosis and treatment of viral hepatitis B and C inUkrainein order to stabilize the epidemic situation, reduce morbidity, disability and mortality, increase the duration and quality of patients life.